Chemometric Analysis and Physicochemical Composition of Foreign and Tunisian Olive Oil: Consumer Preferences - Kaouther Ben-Hassine; Islem Yangui; Wissem Mnif; Ameni Taamalli; Cinzia Benincasa; Naziha Kamoun; Dhafer Malouche (Journal of Food Quality)
This research was conducted to evaluate consumer preferences of seven extra virgin olive oils (EVOOs) from foreign and Tunisian cultivars. Two studies were carried out. The first is a comparative physicochemical characterization of the VOOs tasted by the consumers. The second is a consumer survey where each consumer tasted each VOO six times. Using simple linear regressions, we have performed a new method that gives a pairwise comparison between the oils. It revealed that Coratina and Chetoui cultivars were the most preferred revealing by the high concentration of polyphenols with 468 and 525 ppm, respectively, and Arbequina was the less preferred with 182 ppm. We have then performed a principal component analysis on the data composed by the physicochemical parameters that highly discriminate between cultivars. The latter showed important differences between the most and the less preferred oils and that oxidative stability, palmitic, palmitoleic, oleic, and linoleic fatty acids, triacylglycerol, β-carotene, and polyphenols seem to be the principal-choice drivers for consumers.